(untitled) (Applied Biological Research, 2020)
Several phytal extracts in Ayurveda are used in controlling certain allergies and bronchial disorders. In present study, the suspected anti-allergic activity of a tropical perennial tree, jackfruit (Artocarpus heterophyllus Lam), roots were evaluated against allergens that cause bronchial allergy/asthma. The chemical composition of phytal extracts indicated the presence of alkaloids, flavonoids, phytosterols, etc. with suspected anti-allergic capabilities. The binding capabilities between extracts, indoor fungal antigens and human antibodies (Ig E) based on different immunoassays indicated that jackfruit root protein of 75 kDa can be considered as possible and novel treatment option for common respiratory allergies.